Resilient load frequency control design: DoS attacks against additional control loop. (February 2020) - Cheng, Zihao; Yue, Dong; Hu, Songlin; Huang, Chongxin; Dou, Chunxia; Chen, Lei
Highlights: The dynamic of multi-area LFC system with uncertainty and GRC under DoS attacks and time delay is described by a switched delay system. To analyze the resilience of LFC system, we combine the piecewise Lyapunov-Krasovskii functional method and switched system method. A criterion is derived to estimate the tolerable DoS attacks: attacks frequency, uniform bound of sleep intervals and attack intervals. Under the criterion, the design method of resilient LFC control gain is given by using LMIs techniques. Abstract: Resilient load frequency control (LFC) design problem is concerned for a multi-area power system with uncertainty and physical constraint under denial-of-service (DoS) attacks and transmission delay. LFC scheme consists of a local PI control loop and additional control loop to be designed. PI control loop is subjected to constant transmission delay while additional control loop is subjected to DoS attacks. We characterize DoS attacks by attack frequency, uniform lower bound of sleep interval and uniform upper bound of attack interval. Considering DoS attacks and time delay, we describe LFC system dynamic by a switched delay system model. Further, a stability criterion is derived by using delay system method and switched system method. Under the criterion, a design method is presented to solve state feedback control gain. Finally, numerical simulations are given to verify the validness of our proposed design method.